Self-controlled learning: Current findings, theoretical perspectives, and future directions - Ste-Marie, D. M.; Carter, M. J.; Yantha, Z. D. (Skill acquisition in sport: research, theory and practice, 2020)
In conclusion, selfcontrolled learning appears to be advantageous under a variety of learning conditions. There is sufficient evidence, both with laboratory-based tasks and more applied sport-based tasks, to provide informed recommendations for those involved in motor skill acquisition. Currently, it is reasonable to suggest that coaches do not need to prescribe all details of a practice and that learners can be provided varied choices, with relevant instructional resources available to them, in their practice contexts. There still remains, however, a number of unanswered questions and further research on the topic will only move us toward a better theoretical and practical understanding of self-controlled learning.